Growth dynamics of container seedlings of Eucalyptus grandis x Eucalyptus urophylla and Hymenaea courbaril L. - Lima Rocha, Maria Eunice; Pinguelli Ristau, Ana Carolina; Fortado Vera Cruz, Maria Soraia; Ferreira de Oliveira Neto, Cândido; de Matos Malavasi, Marlene; Contro Malavasi, Ubirajara (Revista Ceres, 2022)
Growth analysis (GA) is used to quantify plant development based on morphophysiological changes. GA is a practical tool to evaluate nursery techniques to make them more efficient. The objective of this essay was to quantity measure morphophysiological growth variables of Eucalyptus grandis x Eucalyptus urophylla and Hymenaea courbaril (jatoba) container seedlings to characterize growth stages. The essay was conducted in a shade house located in the western state of Paraná. GA analyses were performed at 10-day intervals on seedlings of both species. When evaluating Hymenaea courbaril seedlings results indicated increased values of height, diameter, root and shoot dry biomass up to 130 days after emergence (DAE). Seedling growth stage-based GA were 70, 100 and 130 DAE for the Eucalyptus hybrid and 50, 80, and 110 DAE for jatoba which presented accelerated, intermediate and reduced seedling growth.